Rare reaction channels in real-time time-dependent density functional theory: the test case of electron attachment - Lacombe, Lionel; Huong Mai Dinh, P.; Reinhard, Paul-Gerhard; Suraud, Eric; Sanche, Leon (European Physical Journal D, 2015)
Abstract We present an extension of standard time-dependent density functional theory (TDDFT) to include the evaluation of rare reaction channels, taking as an example of application the theoretical modelling of electron attachment to molecules. The latter process is of great importance in radiation-induced damage of biological tissue for which dissociative electron attachment plays a decisive role. As the attachment probability is very low, it cannot be extracted from the TDDFT propagation whose mean field provides an average over various reaction channels. To extract rare events, we augment TDDFT by a perturbative treatment to account for the occasional jumps, namely electron capture in our test case. We apply the modelling to electron attachment to H2O, H3O+, and (H2O)2. Dynamical calculations have been done at low energy (3-16 eV). We explore, in particular, how core-excited states of the targets show up as resonances in the attachment probability. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-07-24